Caracterização morfológica dos frutos e sementes de algumas espécies de plantas lenhosas da família leguminose (Caesalpinioideae, Papilionoideae) suas relações abióticas e bióticas de dispersão e o papel na dieta da fauna frugívora / - Díaz-Bardales, María del Pilar (Instituto Nacional de Pesquisas da Amazônia - INPA, 2001)
Morphological studies of fruits and seeds of some species of woody plants of the leguminose family were carried out, with emphasis on the co-evolutionary adaptations in the seed dispersal and predation part; besides information on habit, habitat and distribution, relating their morphology to the type of abiotic and biotic dispersion, and the role of the fruit diet in the frugivorous fungus.
Keywords: Leguminosas; Caesalpinioideae; Mimosoideae; Morfologia; Dispersão e pradação de sementes